GEM-loaded magnetic albumin nanospheres modified with cetuximab for simultaneous targeting, magnetic resonance imaging, and double-targeted thermochemotherapy of pancreatic cancer cells - Wang L (Dove Medical Press, 2015)
Ling Wang,1 Yanli An,2 Chenyan Yuan,3 Hao Zhang,2 Chen Liang,2 Fengan Ding,2 Qi Gao,1 Dongsheng Zhang4 1Department of Ultrasonography, Zhong Da Hospital, Medical School, Southeast University, Nanjing, People’s Republic of China; 2Medical School, Southeast University, Nanjing, People’s Republic of China; 3Department of Clinical Laboratory, Zhong Da Hospital, Medical School, Southeast University, Nanjing, People’s Republic of China; 4Jiangsu Key Laboratory for Biomaterials and Devices, Medical School, Southeast University, Nanjing, People’s Republic of China Background: Targeted delivery is a promising strategy to improve the diagnostic imaging and therapeutic effect of cancers. In this paper, novel cetuximab (C225)-conjugated, gemcitabine (GEM)-containing magnetic albumin nanospheres (C225-GEM/MANs) were fabricated and applied as a theranostic nanocarrier to conduct simultaneous targeting, magnetic resonance imaging (MRI), and double-targeted thermochemotherapy against pancreatic cancer cells. Methods: Fe3O4 nanoparticles (NPs) and GEM co-loaded albumin nanospheres (GEM/MANs) were prepared, and then C225 was further conjugated to synthesize C225-GEM/MANs. Their morphology, mean particle size, GEM encapsulation ratio, specific cell-binding ability, and thermal dynamic profiles were characterized. The effects of discriminating different EGFR-expressing pancreatic cancer cells (AsPC-1 and MIA PaCa-2) and monitoring cellular targeting effects were assessed by targeted MRI. Lastly, the antitumor efficiency of double/C225/magnetic-targeted and nontargeted thermochemotherapy was compared with chemotherapy alone using 3-(4, 5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) and flow cytometry (FCM) assay. Results: When treated with targeted nanospheres, AsPC-1 cells showed a significantly less intense MRI T2 signal than MIA PaCa-2 cells, while both cells had similar signal strength when incubated with nontargeted nanospheres. T2 signal intensity was significantly lower when magnetic and C225 targeting were combined, rather than used alone. The inhibitory and apoptotic rates of each thermochemotherapy group were significantly higher than those of the chemotherapy-alone groups. Additionally, both MTT and FCM analysis verified that double-targeted thermochemotherapy had the highest targeted killing efficiency among all groups. Conclusion: The C225-GEM/MANs can distinguish various EGFR-expressing live pancreatic cancer cells, monitor diverse cellular targeting effects using targeted MRI imaging, and efficiently mediate double-targeted thermochemotherapy against pancreatic cancer cells. Keywords: gemcitabine, Fe3O4 nanoparticles, theranostic nanocarrier